(untitled) (Revista Educação, Artes e Inclusão, 2020)
From the classic dramaturgies and their stagings orbiting around the text, to post-modern and contemporary dramaturgies, with their performative dimensions that make room for a collective writing jointly with the onlookers, the concept of dramaturgy has undergone a process of opening-up proportional to that of the passage of time. The word "dramaturgy" has lost its textual primacy granted by Euro-Centrism to open itself up to somatic manifestations, transforming themselves into happenings. The new spectator of contemporary dramaturgies plays a fundamental role in the creation of writing, which, from the individual, becomes collective, and may, in performance, reach the point of changing the performative programme initially proposed by the artist. I would like to think, at this point, in terms of the concept of dramaturgy in the performance field, and, more specifically, in the field of relational and participatory performance. Contemplating a European participatory performance art project, in which I was a guest artist, I will reflect on the possible constitution of a "Solidarity Dramaturgy", which could encompass or lead to the broader field of “Art of Care”, making room for new artistic possibilities. To develop this reflection, I have chosen the form of diary, a witness of this cartographic research that seeks its objectives through a retelling of the events. I offer you an invitation to join me on this journey. Shall we dance to the rhythm of the writing together?